Rail transport infrastructure in Colombia: current issues, problems, policies and prospects - Quintero González, Julián Rodrigo; Salomón Molano, Mónica Marcela (Uptc, 2023)
The availability of competitive rail infrastructure makes possible the progress and economic and social growth of countries, their territories, regions and cities. However, its development in Colombia is still scarce. The objective is to make a reflection about the strategies that allow the development of the railway infrastructure in the country. The methodology consists of a synthesis of the development and current figures from governmental entities; the perceptions of experts in relation to current problems; and the applicable regulatory and public policy instruments. Based on these elements, a proposal of strategic pillars for the development of railroad infrastructure in Colombia is formulated. It is concluded that regulations and public policies are necessary to enable the implementation and development of the proposed strategies, which are in line with the most recent vision of railroad development proposed by government authorities.